Business Intelligence: Development of a performance monitoring dashboard in a pharmaceutical company - Cerqueira, Filipa Delgado Bizarro (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics